Hildegard of Bingen: A Case Study in Sainthood, Authority, and Change - Frauenhofer, Ella M. (Tufts Archival Research Center, 2020)
An undergraduate senior thesis for the Department of Religion on how both academic and formal religious interest in Hildegard of Bingen relate to how authority is constructed in Roman Catholicism.